Pengaruh Dana Bagi Hasil, Dana Alokasi Umum, Dana Alokasi Khusus, Dana Otonomi Khusus, Dana Desa, dan Belanja Daerah terhadap Kemiskinan di Kawasan Papua - Diah Setyorini Gunawan; Latifah Latifah; Agus Arifin (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Poverty is a complex and multidimensional problem. Papua is an area that has the highest poverty conditions in Indonesia. This research uses panel data consisting of the provinces of Papua and West Papua for the period 2008-2022. The analysis technique used is panel data regression. The results of the analysis show that profit sharing funds and village funds have a negative and significant effect on poverty in Papua. General allocation funds and special allocation funds have a positive and significant effect on poverty. Special autonomy funds and regional spending have no effect on poverty in Papua. The implication of this research is the need to optimize the realization of DAU, DAK, Special Autonomy Funds, and Regional Expenditures so as to reduce poverty levels.